Public-Private Partnerships principles of policy and finance - Yescombe, E. R. (Amsterdam Elsevier, 2010)
"Public-Private Partnerships offers a systematic presentation of the recent trend where Governments look increasingly to the private sector for building and managing infrastructure facilities as well as for providing specialised services. The text covers a wide range of issues, from very general policy ones faced by authorities in considering whether to adopt the PPP route, to much more technical ones, including financial analysis, procurement, financial and legal structuring. Written by an experienced practioner, Mr. Yescombe's represents an invaluable and authoritative guide to all parties involved in PPPs-from investors, bankers, companies providing infrastructure and services to public sector authorities and the public at large as the main user of PPP facilities and/or services. The book will be an excellent introduction for newcomers into the PPP business as well as valuable reference source for all those that already have expereince in the subject."
Includes bibliographical references
Keywords: Public-private sector cooperation